Study of the Main components of the organic matter extracted from the leaves of Syrian Melilotus Officinal plant using GC-MS and their effects on some of Pathogenic Microorganisms (Latakia University Journal -Basic Sciences Series, 2018)
Due to the economical and medical importance of the Melilotus plant and the wide distribution of this plant in the Syria environment, it was of necessity to  study the  the composition of organic matter extracted from the leaves of this plant.The Melilotus Officinal organic matter was extracted and purified their where were studied by  GC-Maas spectrometry.The organic matter was obtained by Soxhlet extractor and by solvent n-Hexane. Components have been found which was about (99.91%) from the total of Essential Oil.The major components were extracted by Soxhlet extractor and the following components were determined : n-Docosane(39.82%) , Hydrocoumarin(15.39%) ,Methyl 3-(2-hydroxyphenyl)propionate(14.29%).The major components were determined by solvent n-Hexane:1,2-Benzenedicarboxylic acid(17.77%)   ,   9,12,15-octadecatrienoic acid(12.85%)The effects of the extracted aromatic oil from the leaves of  Melilotus plant on some of Pathogenic Microorganisms were studied.